2003
DOI: 10.1002/mar.10093
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analytic investigation of contrast effects in decision making

Abstract: Several theoretical perspectives and numerous experiments illustrate the influence of context on social judgment. Debate ensues, however, when researchers attempt to describe mechanisms that lead persons to contrast current decisions with prior judgments. The purpose of this study is to summarize and qualify prior analyses of the influences of context on judgment. Procedural conditions, stimuli type, and priming conditions are implicated as factors that moderate the main effect of extremity on contrastive judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example, Nieuwenstein et al (2015) described a meta-analysis of studies on the 'unconscious thought' effect and concluded that, despite many positive findings (e.g., Dijksterhuis, Bos, Nordgren, & van Baaren, 2006), the true effect size after correcting for publication bias is negligible. Renkewitz, Fuchs, and Fiedler (2011) reanalyzed a meta-analysis by Dato-on and Dahlstrom (2003) on priming effects in decision making and found evidence of publication bias, leading them to conclude that Dato-on and Dahlstrom had overestimated the true effect size. And Carter and McCullough (2014) reported a meta-analysis which implied that -after correcting for publication bias -the tendency for acts of self-control to cause 'depletion' of a common resource has an effect size that is no greater than zero.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nieuwenstein et al (2015) described a meta-analysis of studies on the 'unconscious thought' effect and concluded that, despite many positive findings (e.g., Dijksterhuis, Bos, Nordgren, & van Baaren, 2006), the true effect size after correcting for publication bias is negligible. Renkewitz, Fuchs, and Fiedler (2011) reanalyzed a meta-analysis by Dato-on and Dahlstrom (2003) on priming effects in decision making and found evidence of publication bias, leading them to conclude that Dato-on and Dahlstrom had overestimated the true effect size. And Carter and McCullough (2014) reported a meta-analysis which implied that -after correcting for publication bias -the tendency for acts of self-control to cause 'depletion' of a common resource has an effect size that is no greater than zero.…”
Section: Discussionmentioning
confidence: 99%